O limite de atuação do Instituto Nacional da Propriedade Industrial no registro dos contratos de transferência de tecnologia - Gustavo Redo Monteiro (2014)
This study aims to analyze the legitimacy of state intervention through the Instituto Nacional da Propriedade Industrial INPI (National Institute of Industrial Property) at the moment of the filling technology transfer contracts. The main issue of this study is to assess whether the INPI has standing to intervene of the relationship between individuals, in transactions involving the commercialization of technology. There was a significant change in the purpose of the institution with the enactment of the Law number 9279/96, which expressly suppressed the function of INPI to adopting measures to regulate the technology transfer. For this studys purpose, will matter the of technology transfer in the strict sense, ie, contracts that effectively involve providing technical knowledge (know-how). The need of the research is based on the fact that Brazil is a country that is not recognized like a country that innovates, and its economy is based on the export of commodities and products with low technologies content. Thus our objectives is, at first, to demonstrate that the optimal path of the country to reach the technological pairing to industrialized countries, is to stimulate the exchange of technology through the acquisition of ready and testes technologies, decreasing the risks and the costs involved in the process of innovation. This policy resembles the technological trajectory of other countries that have achieved great success in shifting the paradigm from being economically underdeveloped to become industrially developed countries. The acquisition of ready and tested technologies provides the accumulation of knowledge, creates familiarity and ultimately enables improvement of the technology acquired. Additionally, we intend to address the existing legal uncertainty on this subject due to the not uncommon intervention of the INPU in contracts conditions, negotiated between the parties for the licensing of technologies, such as the settlement of prices royalties. This uncertainty is reflected in the few, but very different, existing adjudicated on the subject to date.. At the end, we seek to demonstrate that the INPI lacks legitimacy to intervene in negotiations made by individuals in economic transactions of technology, leaving the restricted legitimate purpose of analyzing the merits exclusively to impair the regulation of rights and obligations issues related to industrial property itself patents, industrial designs, trademarks and geographical indications, according to the law.